“Survival” of the fittest, “sheltering” of the mightiest: competition and regulation in contemporary urban housing markets - Brandl, Erika (Porównania, 2024)
This essay mobilizes popular insights about the “law of the jungle” to conceptualize and critique prevalent consumption and policy attitudes in urban environments, with a focus on residential infrastructure. A phrase used metaphorically to describe a given situation where competition, aggression, and “survival of the fittest” prevail, it is here used in order to formulate a new characterization of contemporary cities as environments where there is minimal housing regulation or oversight (architectural occupation as survival-of-the-fittest battle), and where individual dwellers are left to operate without significant constraints. In the first section of the paper, I introduce a commonplace interpretation of the “jungle metaphor”, commenting on sets of characteristics and values which are associated with it. In the second section of the paper, I paint a portrait of contemporary socio-economic environments, with a focus on urbanity and its distributive ordering of housing resources. I describe these environments as constructed (formal arrangements; architecture and urbanism) and policed (institutional arrangements; governments and state authorities) in manners which acutely—and problematically—emphasize market laissez-faire and self-interest. In the third section of the paper, I link this portrait of the contemporary city to survival-of-the-fittest jungle-like spaces, commenting on rivalrous competition between dwellers and, in the fourth and concluding section, I briefly propose one possible, normatively desirable form of urban market regulations.